Induced ovulation and rearing of the pacu (Colossoma mitrei) - Castagnolli, Newton [UNESP]; Donaldson, Edward M. (Elsevier, 1981)
A method is described for spawning the economically important Brazilian characin species Colossoma mitrei. Ovulation was induced using a priming injection of 0.2 mg/kg partially purified gonadotropin SG-G100 followed at 8 h by injecting an extract of 20 mg/kg acetone-dried chum salmon pituitary powder. Spermiation was induced in the male using a similar primer followed by 14 mg/kg acetone-dried chum salmon pituitary powder. Eggs were successfully fertilized and incubated at 25-26°C. Hatching occurred at 20.5 h and a survival of 10% to fingerling size was achieved. © 1981.